Optimasi dan Validasi Ketinggian Air di Rotary Water Immersion Retort pada Proses Pasteurisasi Minuman Rasa Buah - Kurniawan, Puteri Stevia Nutrihaliza; Rahayu, Winiati P. (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Blackcurrant smoothie beverages produced by PT XYZ has water activity >0.85 and acidity levels ranging from 3.8–4.2. The preservation of this product can be achieved through pasteurization to eliminate the target microorganism that can survive at pH below 4.6. PT XYZ implements a water immersion retorts system for pasteurization. One of the critical parameters for sufficient heat in this type of retort is the water level. This study aims to evaluate the current standard water level, which was relatively high (70%), to achieve a more efficient process, as well as the validation of heat adequacy and product safety. The water level targets (45, 55, and 65%) were achieved by reducing the filling step time, which was determined by comparing the average existing water level to the target water level. The evaluation of heat adequacy was conducted by comparing the process pasteurization value with the standard pasteurization value using the 5D microbial reduction cycle concept. The results revealed that pasteurization with water levels below the current standard was sufficient to reduce Escherichia coli (E. coli) and Bacillus polymyxa (B. polymyxa). At water levels of 55 and 65%, validation was confirmed through the total plate count (0 CFU/mL) and E. coli (0 MPN/mL) analysis, which meet the required standards for blackcurrant smoothie beverages.